THE APPLICATION OF DICTOGLOSS TECHNIQUE TO IMPROVE THE EIGHTH GRADE STUDENTS’ WRITING SKILL IN SMP NEGERI 31 MEDAN - Siagian, Jessica Hieronima; Lumban Raja, Viator; Sembiring, Novalina (Kairos English Language Teaching Journal, 2020)
Writing is the most important human invention which provides a relatively permanent record of information, opinions, benefits, feelings, arguments, explanations, and theories. Many students are still confused how to write a text because they do not know the rules and they can not express their ideas into written form. One of the techniques to improve studentsâ€™ writing skill is Dictogloss Technique. The method that is used in this research is Classroom Action Research (CAR). The subject of this research are 35 students of class VIII-4 of SMP Negeri 31 Medan in the academic year of 2018/2019. Tests, observation sheets, field notes, and questionnaire were used as the instruments for collecting the data. The result of this study showed increasing score of studentsâ€™ writing descriptive text. The result of the test showed that the studentsâ€™ mean score in pre-test is 60 with 0% students got score 75, in formative test the mean score is 76.71 with 60% students got score 75 and in post-test the mean score is 80.85 with 94% students got score 75. It showed that the percentage improvement of the studentsâ€™ mean score from pre-test to post-test was 94%. The response of students after being taught by using Dictogloss Technique are good. The students enjoyed the process of teaching and learning. It is suggested that teachers use Dictogloss Technique in teaching writing skill to improve studentsâ€™ skill in writing descriptive text. Â